Diseño de una red de infraestructura verde en los cerritos del cantón Santa Lucía - Verdezoto Cabello, Keril Alexa (2024)
The objective of this project is to present a design prior to obtaining the title. Focused on developing a network of green infrastructure in Los Cerritos del Canton Santa Lucia, with which it is intended to improve the current conditions and make efficient use of available areas. The proposal includes the creation of spaces for recreation, social interaction and contact with nature, thus providing health benefits that are not currently present in the area. The design is based on the principle of a green and sustainable approach, with a strategic distribution to ensure a safe and healthy environment. It also contemplates the implementation of 3R (Reduce, Reuse, Recycle) practices. This project is expected to boost economic development, tourism, and local commerce, promoting social and economic progress in the Cerritos area of the Santa Lucia canton.